Associations of sport participation and training volume with overuse injuries in Japanese male youth soccer players: Implications for early sport specialization - Nakaichi, N.; Sugimoto, D.; Numa, D.; Kotani, R.; Nakamura, H.; Akiyama, K.; Hirose, N. (Sports Health: A Multidisciplinary Approach, 2025)
Background: Sport specialization is associated with increased risk of overuse injuries. However, the effects of sport specialization on the risk of overuse injury may differ by specific sport and sociocultural parameters. This study aimed to determine the associations of sport participation and training volume with previous overuse injuries in Japanese male youth soccer players.